Solve for \( x \), Check your solution, \[ 12 x=-33+69 \] \( x=\square( \) Simplify your answer.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve for \( x \) in the equation \( 12x = -33 + 69 \), first simplify the right side: \[ -33 + 69 = 36 \] Now, replace the right side in the equation: \[ 12x = 36 \] Next, divide both sides by 12 to isolate \( x \): \[ x = \frac{36}{12} = 3 \] Checking the solution, substitute \( x = 3 \) back into the original equation: \[ 12(3) = -33 + 69 \] Calculating both sides gives: \[ 36 = 36 \] Since both sides are equal, the solution is verified. Thus, the final answer is: \( x = 3 \)